Gobierno corporativo en mercados emergentes: impacto en la Bolsa de Valores de Lima - BVL - Burneo Farfan, Kurt (2016)
Nowadays, the international financial landscape has undergone several developments with systemic implications, such as the financial crisis of 2007 and 2008, the slowdown in China (2014 to date), the contraction of the BRICS (2013 to date ), among others, as fundamental to the future of the economies is the performance of firms, it happens that behind these events happen several factors, one of them, poor implementation of good practices and corporate governance and this has led to that the international community put emphasis on ways of conducting business transactions. NGuyen & Xiangkang (2015) state that the main evidence of the effects of not implementing good corporate governance practices are tangibly evident in those countries which have now been multiplied their productivity, already affected by the Subprime Crisis. This work aims to try to answer the question of whether indeed the application of the principles of good corporate governance would have the effect, differentially favorable results with respect to those entities that did not apply these.